Enhanced buffer management policy and packet prioritization for wireless sensor network - Rabileh A.A.; Abu Bakar K.A.; Dahnil D.P.; Mohamed R.R.; Mohamed M.A. (Insight Society, 2023)
Limited storage of the sensor node is one of the main causes of packet drop in the Wireless sensor network (WSN). Frequent link disconnection is also another cause of packet drop. Due to lack of continues end-to-end connection; neighbouring nodes might not be able to connect with one another. Hence, communication may be setup with the help of store and forward approach between the source and destination. In that case, the sensor node may not be capable of storing a chunk of data since the buffer is available in a small amount. In order to store the data packets in the buffer when the link is down, an effective buffer management scheme is highly needed to keep the data packets for a long time until the link is re-established. This paper proposes a new buffer management scheme called Packet Priority Heterogonous Queue (PPHQ), which based on prioritizing and classifying the packets into different categories to minimize the loss of important packets. Unlike the existing Multi-layer WSN, that treats the data packets differently; we considered the data packets such as; temperature, humidity, and pressure to be same. However, the classification of different packet types is based on the sensor's information value. We completely divide the whole buffer into different queues, and thus the newly arrived packets are inserted in their corresponding queue. The buffer will then prioritize and schedule on which packet to be stored or transmit first when the buffer is overloaded. Our result exhibits that PPHQ scheme indeed provides minimum packet drop as well as maximum throughput compared to existing Multi-layer WSN buffer management schemes. 2018, Insight Society.